IMPROVING STUDENTS’ ACHIEVEMENT IN READING NARRATIVE TEXT THROUGH APPLICATION OF JIGSAW STRATEGY - Siti Fitri Hasibuan; Sri Rahma Yani Harahap (Journal of Educational Science Learning and Research, 2025)
This study was aimed to find out the improvement of students’ achievement in reading narrative text by using Jigsaw Strategy at Mts Swasta Al husna. The subject of this study was grade IX of Mts Swasta Al husna . It was consisted of 32 Students. The objective of the study was to improve the students’ achievement in reading Narrative text by using Jigsaw Strategy. The research of this study was conducted by using Jigsaw Strategy in Classroom Action Research. The technique of analyzing the data of this research is applied qualitative and quantitative data. The qualitative data were taken from diary notes, interview sheet, observation sheet and documentation. The quantitative data were taken from reading test. In the pre-test the student’s gotten up 65 there were only 2 of 32 students (6,25%). In the post-test of cycle 1, students who got up 65 there were 8 of 32 students (25%). It means that there was improvement about 18,75%. In the post-test of cycle II, students who got up 65 there were 29 of 32 students (90,62%). The improvement was about 65,62%. The total improvement of the students’ score pre-test to post test of cycle II was 84,37%. In another words, the students got the better score to the next meeting. Based on the finding, the alternative hypothesis was accept. It means, that jigsaw strategy could improve students’ achievement in reading Narrative text.